EFFECT OF DIVIDEND POLICY (DPR), LIQUIDITY (CR) AND PROFITABILITY ON SHARE PRICE AT TRADE, SERVICE AND INVESTMENT SECTORS AT INDONESIA STOCK EXCHANGE IN PERIOD OF 2014-2018 - Ariesa, Yeni; Br. Sitepu, Yolanda Pebrina Cristy (JEBIM Prima, 2020)
Stock price is one indicator that shows investor interest in owning a company's stock. An investor always expects a stable stock price and has a pattern of movement that tends to rise from time to time, but in fact the stock price tends to fluctuate. Fluctuating stock prices become a risk for investors. Therefore, an investor must understand the issues that must be considered in determining investment decisions. The research variables are Dividend Payout Ratio (DPR), Liquidity (CR), and Profitability (NPM) and Share Prices. The research populations were Trade, Service and Investment Sector Companies listed on the Indonesia Stock Exchange in 2014-2018. The research samples were drawn by using a purposive sampling technique. The research samples were 17 company financial statements that met the criteria as a sample of the company. The datacollection was performed by documentation techniques and the research data were analyzed by using multiple linear analysis. Hypothesis testing shows that the Individual Payout Ratio (DPR) and Liquidity (CR) do not have a significant effect on stock prices. Profitability (NPM) has a significant effect on Stock Prices. The value of Adjusted R Square was 0.275 indicating that variations in the DPR, CR, and NPM can explain variations in the variable Stock Price up to 27.5% while the remaining 72.7% can be explained by other factors outside the variables that have not been examined.